The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.6061/clinics/2013(05)06
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in non-adherence among Brazilian patients initiating antiretroviral therapy

Abstract: OBJECTIVE:We conducted a study to identify gender differences in factors associated with the first episode of non-adherence in the 12 months following the first antiretroviral prescription.METHODS:A concurrent prospective study of patients initiating antiretroviral therapy in Brazil was conducted from 2001-2002. The self-reported measurement of adherence was defined as an intake of less than 95% of the prescribed number of doses. Only the first occurrence of non-adherence was considered in this analysis. All a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
3
15
0
5
Order By: Relevance
“…This low level of non-adherence to ART highlights the success of the national ART program in Kenya, where non-adherence levels are lower than reported in other sub-Saharan African countries, including: Rwanda, where 23% of ART patients were non-adherent based on 30-day recall [14]; Ghana, where 14% of ART patients were non-adherent [15]; rural Zambia where 40% of ART patients were not adherent [16], and a pooled analysis of African adherence studies, where overall non-adherence levels were reported to be 23% [17]. Data from developed countries also suggest higher non-adherence levels, with estimates of 45% in a pooled analysis of adherence studies in North America [17], 37% in Sweden [18], 34% in Brazil [19], and 43% in Spain [20]. Studies that have combined indicators of dose, timing, food and other measures have also generally reported higher non-adherence rates, [2122].…”
Section: Discussionmentioning
confidence: 99%
“…This low level of non-adherence to ART highlights the success of the national ART program in Kenya, where non-adherence levels are lower than reported in other sub-Saharan African countries, including: Rwanda, where 23% of ART patients were non-adherent based on 30-day recall [14]; Ghana, where 14% of ART patients were non-adherent [15]; rural Zambia where 40% of ART patients were not adherent [16], and a pooled analysis of African adherence studies, where overall non-adherence levels were reported to be 23% [17]. Data from developed countries also suggest higher non-adherence levels, with estimates of 45% in a pooled analysis of adherence studies in North America [17], 37% in Sweden [18], 34% in Brazil [19], and 43% in Spain [20]. Studies that have combined indicators of dose, timing, food and other measures have also generally reported higher non-adherence rates, [2122].…”
Section: Discussionmentioning
confidence: 99%
“…The psychological changes often associated with HIV and their predictive factors are mood disorders, anxiety, depression, stress related to the health-disease process, history of psychiatric disorder, drug use and suicide in the family. Social support and early detection of those factors and symptoms of psychological distress, quality of life and adherence to treatment where are essential so that they do not adversely affect the treatment adherence and quality of life of people living with HIV/AIDS (PLHA) [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The Brazil is the country in Latin America with the largest number of reported cases since the beginning of the epidemic, being logged, according to the Ministry of health (MS) from 1982 until June 2014, 656,701 cases of AIDS [2,3]. On the other hand, has advanced in public policies to combat the disease, with the support of international agencies, becoming focus of civil society organizations, philanthropic, religious, among others [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Joint United Nations programme on HIV/aids (UNAIDS) worldwide there is 35.3 million people living with HIV. It is estimated that 0.8% of adults aged 15-49 years in the world living with the virus and 9,700,000 people are in treatment [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation